Multiple Indolent Purplish Nodules and Plaques of the Extremities in an 85-year-old Man: A Quiz - Giulia Coscarella; Giorgia Merlini; Mario Alessandri Bonetti (Medical Journals Sweden, 2024)
Abstract is missing (Quiz)